2011
DOI: 10.1016/j.wem.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Snowboarding Injuries in Australia: Investigating Risk Factors in Wrist Fractures to Enhance Injury Prevention Strategies

Abstract: Abstract:Objective: To investigate risk factors associated with wrist fractures in snowboarders to inform future snowsport safety strategies.Design: A prospective case-control study using a non-probability convenience sample was conducted with data collected via a respondent completed questionnaire. Those presenting with injuries other than wrist fractures acted as the control.Participants: Snowboarders with a snowboard-related injury who presented to one of 10 medical centres and physiotherapy clinics in reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…A wide range of risk factors have been investigated in a number of studies including modifiable factors such as helmet use [32,10,30,[33][34][35][36], wrist guard use [37][38][39]6, 40], ability [41,42], alcohol use [43,44] and terrain condition [45][46][47][48]. Non-modifiable factors such as age [49][50][51], sex [52][53][54][55] and weather [56,57,29] have also been examined.…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of risk factors have been investigated in a number of studies including modifiable factors such as helmet use [32,10,30,[33][34][35][36], wrist guard use [37][38][39]6, 40], ability [41,42], alcohol use [43,44] and terrain condition [45][46][47][48]. Non-modifiable factors such as age [49][50][51], sex [52][53][54][55] and weather [56,57,29] have also been examined.…”
Section: Resultsmentioning
confidence: 99%
“…Yet even with the observed effectiveness of wrist protectors and the ability to purchase or rent wrist protectors, the rate of wrist injuries has remained fairly constant at 19-28 % of all snowboard related injuries [54]. One reason for the constant wrist injury prevalence may simply be that the use of wrist protectors remains relatively low, with worldwide estimates ranging from approximately 11-42 % of interviewed snowboarders both on-and offpiste [12,35,39,40,69,[73][74][75][76][77][78]. Importantly, the rate of wrist protector use was much lower, between 1 and 18 %, for wrist injured snowboarders [26,72,76,[79][80][81].…”
Section: Wrist Injuries In Snowboardingmentioning
confidence: 99%
“…One reason for the constant wrist injury prevalence may simply be that the use of wrist protectors remains relatively low, with worldwide estimates ranging from approximately 11-42 % of interviewed snowboarders both on-and offpiste [12,35,39,40,69,[73][74][75][76][77][78]. Importantly, the rate of wrist protector use was much lower, between 1 and 18 %, for wrist injured snowboarders [26,72,76,[79][80][81]. Engel and Langran reported that paediatric snowboarders who sustained wrist injuries while wearing wrist protection had a higher self-reported ability than injured riders not wearing wrist protectors [81].…”
Section: Wrist Injuries In Snowboardingmentioning
confidence: 99%
See 2 more Smart Citations